2022
DOI: 10.1002/jmri.28495
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Changes of the Breast Cancer Screening Paradigm

Abstract: Since four decades mammography is used for early breast cancer detection in asymptomatic women and still remains the gold standard imaging modality. However, population screening programs can be personalized and women can be divided into different groups based on risk factors and personal preferences. The availability of new and evolving imaging modalities, for example, digital breast tomosynthesis, dynamic‐contrast‐enhanced magnetic resonance imaging (MRI), abbreviated MRI protocols, diffusion‐weighted MRI, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…52,61 Screening is a more complex and resource-intensive strategy that requires adequate capacity and infrastructure to avoid delays in diagnosis and treatment. 62 Screening programs should be undertaken only when their effectiveness has been demonstrated, when resources are sufficient to cover the target group, when facilities exist to confirm diagnoses and ensure treatment, and when the prevalence of the disease is high enough to justify the effort and costs of screening. 60,63 It should be noted that promoting early diagnosis is a necessary prerequisite to implementing population-based screening in certain situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52,61 Screening is a more complex and resource-intensive strategy that requires adequate capacity and infrastructure to avoid delays in diagnosis and treatment. 62 Screening programs should be undertaken only when their effectiveness has been demonstrated, when resources are sufficient to cover the target group, when facilities exist to confirm diagnoses and ensure treatment, and when the prevalence of the disease is high enough to justify the effort and costs of screening. 60,63 It should be noted that promoting early diagnosis is a necessary prerequisite to implementing population-based screening in certain situations.…”
Section: Discussionmentioning
confidence: 99%
“…73 Training is a low-cost strategy that can be used to increase knowledge of BC and BSE, reaching a large number of people with limited resources. 18,62 In terms of health prevention planning, BC awareness, education, public health, and social measures are all important. 27,52 Most people desire effective BC prevention education, which fosters healthy behaviors, not only through teaching, but also through using the breast as a model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating screening MRI performance in these risk populations reported important results, in terms of sensitivity (69%-100%) and specificity (84%-98%), as well as improved early cancer detection ($16/1000 screening examinations) and a strong reduction of interval cancers. [122][123][124] While recommendations do not count MRI as the modality of choice when screening women of average BC risk, it should be noted that these benefits seem to be independent of individualized BC risk. In support of this, a study investigating the possible utility of adjunct MRI in screening women of average risk, demonstrated high specificity (97.1%) and PPV (35.7%) in detecting BCs early in all breast density categories, while reporting 0% of interval cancers.…”
Section: Mri Techniquesmentioning
confidence: 99%
“…Acknowledging the considerable body of evidence available, some professional societies and organizations have broached the use of CE‐MRI in screening the population at intermediate BC risk, including those with extremely dense breasts (Table 2). Studies investigating screening MRI performance in these risk populations reported important results, in terms of sensitivity (69%–100%) and specificity (84%–98%), as well as improved early cancer detection (~16/1000 screening examinations) and a strong reduction of interval cancers 122–124 . While recommendations do not count MRI as the modality of choice when screening women of average BC risk, it should be noted that these benefits seem to be independent of individualized BC risk.…”
Section: Part 2: Novel Imaging Approaches Toward Risk‐adapted Breast ...mentioning
confidence: 99%
“…Similarly, the traditional “one-size-fits-all” approach to breast cancer screening, which is based solely on the age criterion, has become obsolete because it does not take account of the biologic and epidemiologic complexity of the disease [ 9 , 10 ]. Breast cancer is the result of a complex web of causation involving multiple interacting risk factors.…”
Section: Introductionmentioning
confidence: 99%